EFEKTIVITAS NEUROKINETIC EXERCISE TERHADAP PENINGKATAN AKTIFITAS FUNGSIONAL PADA PLANTAR FASCIITIS : NARRATIVE REVIEW - Ade Putri Malahayati Sipayung; Meiza Anniza; Amalia Rakhman (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Plantar fasciitis is the most common cause due to inflammation or degeneration of the plantar fascia. This condition can affect work productivity and disrupt functional abilities. One of the physiotherapy programs to improve functional activity in plantar fasciitis is by providing neurokinetic exercise. The purpose of this study is to present evidence related to the effectiveness of neurokinetic exercise in improving functional activity in plantar fasciitis. The method used in this study is a narrative review using the PICO framework (Population, Intervention, Comparison, Outcome). Journal searches were conducted using PubMed, Science Direct, Scopus, and PEDro. The search results from the 4 databases were based on keywords that had been adjusted. Article selection was done using the PRISMA flowchart, followed by the article assessment stage using critical appraisal and compiling narrative review results. Based on the article search results with reference criteria of the last 5 years, 26 articles were obtained. After screening based on inclusion and exclusion criteria, 10 journals were found to be relevant to the topic, mentioning that neurokinetic exercise can improve functional activity in plantar fasciitis. It is concluded that neurokinetic exercise is effective in improving functional activity in plantar fasciitis. Keywords: Neurokinetic exercise; Functional activity; Plantar fasciitis